The Prognostic Value of serum Crp In Acute Ischemic Stroke Patients - معنا, عبير; عيسى لايقه ,; يوسف زريق , (Latakia University Journal -Medical Sciences Series, 2022)
Purpose : Strokes are the third cause of death and the leading cause of disability around the world. Acute ischemic stroke may trigger an inflammatory response that leads to increased levels of C-reactive protein (CRP). High levels of CRP may be associated with poor outcome because they reflect either an inflammatory reaction or tissue damage. Objective of this study: To evaluate Crp as an independent predictor of functional outcome and stroke severity . Method: The study sample included 206 patients with acute stroke who were admitted to the Neurology Department of Tishreen University Hospital in Lattakia between 2021 and 2022. score. Prognosis was assessed according to mRs after 30 days. Serum CRP was measured within 48 of symptoms onset. Results :There is a statistically significant relationship between the rise of CRP with the severity of stroke according to NIHSS, where the CRP value was higher at the degree of severe infarction, and with the prognosis according to mRS, where the CRP value was higher in the bad prognosis. The most sensitive and specific standard point is the CRP value = 6.45 with a sensitivity of 71.3% and a specificity of 86.4% for predicting a bad prognosis. The highest sensitivity and specificity standard score was a value of CRP=7.85 with 75% sensitivity and 69.5% specificity for predicting death. Conclusion : C-reactive protein (CRP) level is significantly higher in ischemic strokes and higher within 48 hours of symptom onset is a poor prognostic indicator.. The risk of poor outcome or death at 30 days increased with higher levels of CRP. Elevated CRP values is a risk factor in association with other risk factors like diabetes/atrial fibrillation